Analysis of the Implementation of the Contractor Safety Management System (CSMS) in the Implementation Phase at PT X Ogan Komering - Aqila, Syifa; Rifai, Muchamad (Periodicals of Occupational Safety and Health, 2024)
The high intensity of the project and stages of work at PT X Ogan Komering, so it requires contractors and subcontractors to operate in the area. Overall at PT X there are 70% of workers from contractors, so work accidents are more prone to occur in contractor workers, so it is important to ensure that contractors prioritize aspects of Occupational Safety and Health (K3). One approach to achieving this goal is to implement a CSMS, which ensures that contractors include OSH aspects in the project being undertaken. The implementation of CSMS often faces challenges, such as contractors' limited understanding of CSMS, for which efforts are needed to overcome these obstacles and prevent errors among workers that can cause incidents. The design of this study uses a descriptive qualitative method with a case study design with data collection from interviews, observations and document reviews. The Contractor Safety Management System (CSMS) consists of 2 Phases, namely Administration and Implementation, in the Implementation Phase consists of Pre-Work Assessment (PSB), Running Assessment (PB), and Final Assessment (PA). In general, the implementation of CSMS has gone well, this can be seen from the availability of SIKA, SIM-L and there is also Safety Induction as a step to minimize the risk of accidents. The supporting and inhibiting factor in the implementation of CSMS is the awareness of all parties involved. If awareness in the implementation of CSMS is lacking, its implementation will be hampered. The implementation of CSMS has been well underway and has succeeded in increasing OSH awareness and reducing work incidents, but it needs to increase supervision and socialization of contractor workers, especially in high-risk jobs.